The reality of God and the problem of evil - Davies, Brian, 1951- (Continuum, 2006)
An important new book on how we can still believe in a God of love and confront the problem of evil in the world. Probably the most important book on the subject since John Hick's book Èvil and the God of Love.̀ & ; Evil is a strong word that people now employ fairly rarely. Many people believe these days that God is omnipotent, omniscient and good and that what we deem to be bad or evil in the world is no reason for abandoning belief in God. It is an intellectual or theoretical problem not one where the focus is on how one might bring about some desirable goal (a practical matter). & ; Profess.